Research Progress in Lactoferrin’s Role in Alleviating Intestinal Barrier Dysfunction - LI Yi, REN Xinxin, WANG Qin, HE Xiaoyun (Shipin Kexue)
The intestinal barrier plays a crucial role in maintaining homeostasis in the body. When the intestinal mucosa is damaged, the tight junctions between intestinal cells are disrupted, and the intestinal flora becomes imbalanced, a variety of diseases can arise. Natural active proteins are pivotal in the repair of the intestinal barrier. Lactoferrin, a glycoprotein abundant in mammalian milk, exhibits a range of biological functions such as antioxidant, anti-inflammatory and antibacterial functions. Numerous studies have shown that lactoferrin elevates the levels of intestinal tight junction proteins, promotes the growth and development of intestinal cells, down-regulates the expression of inflammatory factors, regulates the immune response and intestinal microbial diversity, and contributes to the maintenance of intestinal barrier homeostasis. In this paper, a review on the alleviation of intestinal barrier dysfunction by lactoferrin is conducted, aiming to gain a better understanding of the mechanisms underlying lactoferrin’s role in alleviating intestinal injury and to provide insights for the development of lactoferrin-based interventions in intestinal diseases.